Increasing coping and strengthening resilience in nurses providing mental health care: Empirical qualitative research - Rudor J. Ramalisa; Emmerentia du Plessis; Magdalena P. Koen (AOSIS, 2018)
Background: Research on coping and resilience is on the rise. However, there is a paucity of information addressing strengths, assets, competence or resilience that enable nurses to remain committed and cope in their profession despite the adversities they face in their working environment.   Objective: The purpose of this research was to explore and describe how to strengthen the resilience of nurses in a work environment with involuntary mental health care users.   Method: An exploratory and descriptive research design, which is contextual in nature, was used.   Results: Narrative responses to two open-ended questions (How do you cope with providing mental health care to involuntary admitted mental health care users? and; How can your resilience be strengthened to provide mental health care to involuntary mental health care users?) yielded coping mechanisms and resilience strengthening strategies.   Conclusion: Nurses caring for involuntary mental health care users are faced with challenging situations while they themselves experience internal conflict and have limited choices available to be assertive. To strengthen their resilience, the following factors should be taken into account: support, trained staff, security measures and safety, teamwork and in-service training and education.